PEMBUATAN MINYAK KELAPA MURNI PENGENDAPAN DI DESA RIBANG KECAMATAN KOTING, KABUPATEN SIKKA - Gahu Lewar, Ferdinandus; Noni, Sarlina; Saputera Wanda, Taras (Universitas Cokroaminoto Palopo, 2024)
Virgin Coconut Oil (VCO) is a modified version of traditional coconut oil production, resulting in a product with low water content and low free fatty acid levels. It is clear in color, has a pleasant aroma, and boasts numerous benefits. The purpose of this study is to enhance the value of coconut as a primary commodity in tropical regions. This process creates opportunities for empowering local communities through small and medium-sized enterprises (SMEs), reducing waste, and supporting environmentally friendly production practices. The VCO produced not only meets local market demands but also holds great potential as an export product, catering to the global trend for natural and organic products. Research on the processing and production of VCO concludes that Virgin Coconut Oil is a coconut derivative with numerous benefits and high economic value. Its simple production process, which uses natural ingredients without chemicals, preserves essential nutrients such as lauric acid, vitamin E, and fatty acids. Compared to regular coconut oil, VCO offers several advantages, including longer shelf life, superior oil quality, and significant health benefits such as antimicrobial and antiviral properties. In addition to its health benefits, VCO contributes to beauty care, including moisturizing skin and hair and addressing various skin issues. Economically, VCO creates opportunities for community empowerment through SMEs, supports eco-friendly production, and has the potential to become a leading export product in the global market.